Negative current collector, negative plate, battery, battery pack and electronic equipment

By setting a primer layer containing active materials, binders and conductive agents on the surface of the metal bottom layer and drying it in a magnetic field environment, the problem of insufficient peeling force between the negative electrode active layer and the current collector is solved, and the conductivity of the negative electrode sheet and battery performance are improved.

CN120600827APending Publication Date: 2025-09-05BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410941767.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

The insufficient peeling force between the negative electrode active layer and the current collector causes the negative electrode active layer to separate during battery processing and use, resulting in battery capacity attenuation and poor electron transmission performance.

Method used

A primer layer is set on the surface of the metal bottom layer. The primer layer is composed of active materials, binders and conductive agents. The content of the binder and conductive agent is controlled to increase the peeling force between the negative electrode active layer and the current collector, and the negative electrode current collector is prepared by magnetic field drying treatment.

Benefits of technology

It improves the peel strength and conductivity of the negative electrode sheet, reduces the resistivity, increases the battery's 50% SOC DC internal resistance and mixed material gram capacity, and extends the service life of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120600827A_ABST
    Figure CN120600827A_ABST
Patent Text Reader

Abstract

The invention provides a negative current collector, a negative plate, a battery, a battery pack and electronic equipment. The negative current collector comprises a metal bottom layer and a bottom coating arranged on at least one functional surface of the metal bottom layer, the bottom coating comprises an active material, a binder and a conductive agent; the active material comprises graphite; in the bottom coating, the content of the binder is 1.2-2 g per 100 g of graphite, and the content of the conductive agent is 0.5-3 g per 100 g of graphite; and the OI value of the negative current collector is not greater than 5. According to the negative current collector provided by the invention, the bottom coating is arranged on the surface of the metal bottom layer, so that the peeling strength between a negative active layer of a subsequent negative plate and the current collector is improved, and the resistivity of the negative plate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode current collector, a negative electrode sheet, a battery, a battery pack and an electronic device. Background Art

[0002] The negative electrode sheet is usually composed of a negative electrode active layer and a current collector. The peeling force between the negative electrode active layer and the current collector is an important prerequisite for ensuring the normal processing and use of the battery. If the current collector does not have enough binding force on the negative electrode active layer, that is, the peeling force between the negative electrode active layer and the current collector is low, during the battery processing or use process, the negative electrode active layer at the edge of the negative electrode may separate from the current collector, resulting in powder loss, causing the battery capacity to decay sharply, thereby leading to battery failure.

[0003] The coated current collector of conventional graphite negative electrodes is a single metal foil. If the negative electrode active slurry is directly coated on the surface of the metal foil, on the one hand, the peeling force between the negative electrode active layer and the current collector is low; on the other hand, the OI value of the prepared graphite negative electrode is high and the electrode tortuosity is high, resulting in poor electron transmission performance of the battery negative electrode sheet. Summary of the Invention

[0004] The present invention provides a negative electrode current collector, which helps to improve the conductivity and peel strength of a negative electrode sheet.

[0005] The present invention also provides a method for preparing the negative electrode current collector. The preparation method can obtain the negative electrode current collector and is simple to operate.

[0006] The present invention also provides a negative electrode sheet comprising the negative electrode current collector. The negative electrode sheet can have high peel strength and good conductivity.

[0007] The present invention also provides a battery comprising the above-mentioned negative electrode sheet, wherein the battery has a low 50% SOC DC internal resistance and a high mixed material gram capacity.

[0008] The present invention also provides a battery pack comprising the battery, which has excellent electrical performance and stability.

[0009] The present invention also provides an electronic device. Since the electronic device includes the battery, the electronic device has excellent electrical performance and a relatively long service life.

[0010] In detail, in the first aspect, a negative electrode current collector comprises a metal bottom layer and a primer layer provided on at least one functional surface of the metal bottom layer; the primer layer comprises an active material, a binder and a conductive agent; the active material comprises graphite; wherein the content of the binder is 1.2-2 g / 100 g 石墨 , the content of conductive agent is 0.5-3g / 100g 石墨; The OI value of the negative electrode current collector is not greater than 5.

[0011] In an optional embodiment, the thickness of the primer layer is L, and L satisfies: 5 μm≤L≤25 μm.

[0012] In an alternative embodiment, 10 μm≤L≤20 μm.

[0013] In an optional embodiment, the content of the binder is 1.3-1.8 g / 100 g 石墨 ;

[0014] And / or, the content of the conductive agent is 1-2.5g / 100g 石墨 .

[0015] In an optional embodiment, the binder contains styrene-butadiene rubber at a ratio of not less than 60 wt %, and the conductive agent contains conductive carbon black at a ratio of not less than 60 wt %.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned negative electrode current collector, comprising the following steps:

[0017] A slurry comprising an active material, a binder, and a conductive agent is applied to at least one functional surface of a metal substrate and dried in a magnetic field to obtain the negative electrode current collector. In a third aspect, the present invention provides a negative electrode sheet comprising the negative electrode current collector described in the first aspect and a negative electrode active layer disposed on at least one surface of the undercoat layer of the negative electrode current collector.

[0018] In a third aspect, the present invention provides a negative electrode sheet comprising the negative electrode current collector described in the first aspect and a negative electrode active layer disposed on the surface of at least one undercoat layer of the negative electrode current collector.

[0019] In a fourth aspect, the present invention provides a battery comprising the negative electrode sheet described in the third aspect.

[0020] In a fifth aspect, the present invention provides a battery pack comprising the battery described in the fourth aspect.

[0021] In a sixth aspect, the present invention provides an electrical device comprising the battery described in the fourth aspect or the battery pack described in the fifth aspect.

[0022] The negative electrode current collector provided by the present invention helps to improve the peeling force between the negative electrode active layer and the current collector of the subsequent negative electrode sheet by providing a primer layer on the surface of the metal bottom layer, and can also reduce the resistivity of the negative electrode sheet.

[0023] Furthermore, the negative electrode sheet provided by the present invention, because it includes the above-mentioned negative electrode current collector, has a higher electrode sheet peeling force and better conductivity compared with conventional negative electrode sheets under the condition that the negative electrode active layer composition is the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort.

[0025] Figure 1 A negative electrode current collector according to a specific embodiment of the present invention;

[0026] In the figure, 01: metal base layer; 02: base coating;

[0027] Figure 2 The negative electrode current collector of Example 1 of the present invention;

[0028] In the figure, 01: metal base layer; 02: base coating;

[0029] Figure 3 A negative electrode sheet according to a specific embodiment of the present invention;

[0030] In the figure, 01: metal base layer; 02: base coating layer; 03: negative electrode active layer. DETAILED DESCRIPTION

[0031] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0032] In order to improve the peeling force between the negative electrode active layer and the current collector of the negative electrode sheet and the conductivity of the negative electrode sheet, the present invention adopts the following technical solutions:

[0033] In the first aspect, the present invention provides a negative electrode current collector, Figure 1 , comprising a metal base layer 01 and a base coating 02 provided on at least one functional surface of the metal base layer; the base coating comprises an active material, a binder and a conductive agent; the active material comprises graphite; wherein the content of the binder is 1.2-2 g / 100 g 石墨 ; The content of conductive agent is 0.5-3g / 100g 石墨 ; The OI value of the negative electrode current collector is not greater than 5.

[0034] Among them, conventional graphite crystals are excited to form 3 SP 2Hybrid orbitals and a single electron that does not participate in hybridization, which can move in the entire hexagonal plane and has metallic bonding properties. Therefore, conventional graphite has strong conductivity along the parallel direction of the current collector. In the present invention, the OI value of the negative electrode current collector is not greater than 5. At this time, the graphite is arranged vertically relative to the metal bottom layer, so that the conductivity and ion diffusion rate of the electrode along its thickness direction are significantly enhanced, but it also reduces the peeling force between the negative electrode active layer and the negative electrode current collector, and worsens the electron transport of the negative electrode sheet in the length direction. For this reason, on the one hand, it is necessary to limit the content of the binder relative to the graphite to improve the peeling force between the negative electrode active layer and the negative electrode current collector, but the content of the binder should not be too high, such as higher than 2g / 100g 石墨 , which will make the resistivity of the negative electrode sheet higher, resulting in an increase in the DC impedance of the battery, thereby deteriorating the battery rate performance; on the other hand, by controlling the content of the conductive agent relative to graphite, the electron transmission capacity of the negative electrode sheet in the length direction is guaranteed, and at the same time, the contact impedance between the current collector and the negative electrode active layer can be reduced, thereby jointly improving the electron transmission capacity of the negative electrode sheet with graphite.

[0035] The OI value of the negative electrode current collector can be measured by X-ray diffraction spectrum of a horizontally placed negative electrode current collector sample (with the bottom coating facing up) at a scanning angle of 10 to 80 degrees. The ratio of the measured 004 characteristic diffraction peak intensity (or integrated area) to the 110 characteristic diffraction peak intensity (or integrated area) is described as the OI value of the negative electrode sheet, that is, b = C 负极集流体 (004) / C 负极集流体 (110).

[0036] Illustratively, the OI value of the negative electrode current collector is any value within the range of 2-5, 2-4, or 2.5-3.5.

[0037] The present invention does not specifically limit the type or source of the graphite. Technicians can choose conventional graphite as electrode materials, such as natural graphite or artificial graphite.

[0038] The above-mentioned metal bottom layer can also be understood as a traditional metal current collector, for example, any one or more of traditional copper foil, titanium foil, tin foil, chromium foil and composite foils of the above metals.

[0039] In one embodiment, the thickness of the primer layer is L, where L satisfies the following: 5 μm ≤ L ≤ 25 μm. If the primer layer is less than 5 μm, the peeling strength between the negative electrode active layer and the negative electrode sheet will be limited. If the primer layer is greater than 25 μm, the conductivity of the negative electrode sheet and the specific capacity of the active material will be impaired.

[0040] In order to further balance the peeling force between the negative electrode active layer and the negative electrode sheet and the conductivity of the negative electrode sheet, in a preferred embodiment, 10 μm≤L≤20 μm.

[0041] Illustratively, L may be selected from any value of 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, and 19 μm.

[0042] In one embodiment, the graphite has a D50 of 3 μm to 12 μm, preferably 5 μm to 10 μm. The D50 of the graphite is the particle size corresponding to 50% (by volume) of the cumulative particle size distribution curve, which can be considered the median particle size of the material and is generally determined by laser diffraction particle size distribution analysis.

[0043] Illustratively, the D50 of graphite is 6 μm, 7 μm, 8 μm, 9 μm, and so on.

[0044] In order to further balance the peel strength between the negative electrode active layer and the current collector of the negative electrode sheet and the conductivity of the negative electrode sheet; in an optional embodiment, the content of the binder is 1.3-1.8g / 100g 石墨 ;

[0045] And / or, the content of the conductive agent is 1-2.5g / 100g 石墨 .

[0046] In a specific embodiment, the binder contains styrene-butadiene rubber at a ratio of not less than 60 wt %, and the conductive agent contains conductive carbon black at a ratio of not less than 60 wt %.

[0047] It can be understood that styrene-butadiene rubber and conductive carbon black are more suitable for the negative electrode current collector of the present invention, that is, a specific content of styrene-butadiene rubber and conductive carbon black is more conducive to balancing the relationship between the peel strength between the negative electrode active layer of the negative electrode sheet and the current collector and the conductivity of the negative electrode sheet. Exemplarily, the above-mentioned binder can also include other binders besides styrene-butadiene rubber, including but not limited to: polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the above-mentioned conductive agent can include other non-graphite conductive agents besides conductive carbon black, for example, at least one selected from acetylene black, Ketjen black, carbon fiber, carbon nanotubes, and metal powder.

[0048] In a second aspect, the present invention provides a method for preparing the above-mentioned negative electrode current collector, comprising the following steps:

[0049] A slurry containing an active material, a binder, and a conductive agent is applied to at least one functional surface of a metal substrate and dried in a magnetic field to produce the negative electrode current collector. The present invention does not impose any particular limitations on the parameters of the magnetic field, as long as the OI of the negative electrode current collector meets the desired range.

[0050] In a third aspect, the present invention provides a negative electrode sheet, Figure 3 , comprising the negative electrode current collector 01 described in the first aspect and a negative electrode active layer 03 arranged on the surface of at least one primer layer 02 of the negative electrode current collector.

[0051] It can be understood that the above-mentioned negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a dispersant; as for the content between them, technicians can adjust them as needed. For example, based on the mass percentage, the above-mentioned negative electrode active layer includes: 94%-97% of negative electrode active material, 1%-2.5% of conductive agent, 1.2%-2.5% of binder and 0.5%-1.5% of dispersant.

[0052] Illustratively, the negative electrode active material may be selected from at least one of graphite, silicon-doped graphite, and lithium titanate; the conductive agent may be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder may be selected from at least one of styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant may be selected from at least one of carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium lauryl sulfate.

[0053] As for the particle size distribution of the above-mentioned graphite, the present invention does not make any specific limitation. For example, the D50 of the above-mentioned graphite can be 5-16μm, specifically including but not limited to: 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.; D99 can be 14-30μm, specifically including but not limited to: 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, etc.; D10 can be 2-10μm, specifically including but not limited to: 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, etc.

[0054] The thickness, surface density, and thickness of the negative electrode active material layer are not specifically limited in the present invention. However, in order to balance the battery capacity, cycle life, and energy density, in one embodiment, the thickness of the negative electrode sheet is 40-120 μm, including but not limited to 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc.; the surface density of the negative electrode sheet is 3-10 mg / cm 2 , specifically including but not limited to: 3.5mg / cm 2 , 4mg / cm2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 , 6mg / cm 2 、6.5mg / cm 2 , 7mg / cm 2 , 7.5mg / cm 2 , 8mg / cm 2 , 8.5mg / cm 2 , 9mg / cm 2 , 9.5mg / cm 2 etc.; the thickness of the negative electrode active material layer is 20-60 μm, specifically including but not limited to: 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, etc.

[0055] The peeling force between the negative electrode active layer and the negative electrode current collector of the present invention refers to the force required for the negative electrode active layer to be peeled off from the surface of the negative electrode current collector. The test method of the bonding force may include the following process: bonding a pressure-sensitive adhesive tape to a stainless steel plate, and then 2 ) is bonded to a pressure-sensitive tape on one side of the negative electrode active material layer of the negative electrode sheet. The tensile testing machine clamps the negative electrode sheet and performs a 180° peeling, and the peeling force required at this time is recorded.

[0056] The method for testing the longitudinal resistivity of the negative electrode sheet may include the following process: the negative electrode sheet is uniformly cut into 4×10 cm samples, the samples are placed in a resistivity test bench, the test pressure is set to 25 kPa, the pressure holding time is 20 s, and the test result is the longitudinal resistivity of the electrode sheet.

[0057] The present invention does not particularly limit the preparation method of the negative electrode sheet. For example, the negative electrode sheet may be prepared by a method including the following steps:

[0058] Graphite, a conductive agent, a binder, a dispersant, and a solvent are mixed to a solid content of 40-50% (by volume), stirred to form a slurry, and then the slurry is coated on at least one undercoat surface of the negative electrode current collector in a magnetic field environment; then, after drying, rolling, and slitting, a magnetically induced graphite negative electrode sheet is obtained.

[0059] As to whether the above coating and / or drying is performed in a magnetic field environment, the present invention does not specifically limit it. In order to further improve the conductivity of the electrode, technicians can choose to perform the coating and / or drying process in a magnetic field environment.

[0060] In a fourth aspect, the present invention provides a battery comprising the negative electrode sheet described in the third aspect.

[0061] It should be noted that the above-mentioned batteries may include but are not limited to single cells, battery modules, battery packs, etc., that is, the actual application form of the battery provided by the present invention may be but is not limited to the listed products, and may also be other application forms. When the battery is a single cell, it includes at least one of a cylindrical battery, a square battery, etc.

[0062] Generally speaking, the above-mentioned battery further includes a positive electrode sheet, a separator and an electrolyte; the positive electrode sheet includes a positive electrode active material, a conductive agent and a binder.

[0063] The gram capacity of the positive electrode active material directly affects the energy density of the battery. The present invention does not particularly limit the positive electrode active material. For example, the positive electrode active material can be selected from commonly used positive electrode active materials in the field, such as one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, and lithium iron phosphate.

[0064] The present invention is not particularly limited to the above-mentioned separator. Any known porous structure separator with electrochemical and chemical stability can be selected, for example, at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The separator can be single-layer or multi-layer.

[0065] The electrolyte comprises an organic solvent and an electrolyte salt. The organic solvent acts as a medium for transmitting ions in the electrochemical reaction, and any organic solvent known in the art for battery electrolytes can be used.

[0066] For example, the organic solvent may be at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). In a specific embodiment, two or more of the above organic solvents may be selected.

[0067] The electrolyte salt, as a source of ions, may be any electrolyte salt known in the art for use in battery electrolytes. For example, the electrolyte salt may be at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium nitrate (LiNO3), and lithium fluoride (LiF).

[0068] The above-mentioned positive electrode sheet, separator and negative electrode sheet can be stacked in sequence to obtain a battery cell, or the above-mentioned positive electrode sheet, separator and negative electrode sheet can be stacked in sequence and then wound to obtain a battery cell; the battery cell is placed in a packaging battery film shell (such as an aluminum-plastic film shell), and the electrolyte is injected into the outer packaging and sealed to prepare the battery of the present invention.

[0069] In a fifth aspect, the present invention provides a battery pack comprising the battery described in the fourth aspect.

[0070] In a sixth aspect, the present invention provides an electronic device comprising the battery described in the fourth aspect or the battery pack described in the fifth aspect.

[0071] It should be noted that the above-mentioned electronic devices can be any conventional devices that require electricity, for example, including but not limited to computers, electric cars, air conditioners, refrigerators, washing machines, microwave ovens, printers, fax machines, etc.

[0072] The technical solutions of the present invention are further illustrated below with reference to specific examples. All parts, percentages, and ratios described in the following examples are based on weight. All reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment. The instruments used in the examples are commercially available.

[0073] The CAS number of styrene butadiene rubber is: 9003-55-8.

[0074] Example 1

[0075] This example provides a negative electrode current collector, combined with Figure 2 , including a copper foil and a primer layer 02 provided on two functional surfaces of the copper foil 01; the primer layer comprises graphite, styrene-butadiene rubber (SBR), conductive carbon black (CB) and carboxymethyl cellulose (CMC), wherein the D50 of the graphite is 8 μm; the CMC content is 2 g / 100 g 石墨 ; SBR content is 1.5g / 100g 石墨 ; CB content is 2g / 100g 石墨 ; The OI value of the negative electrode current collector and the thickness of the primer layer are 15 μm as shown in Table 1.

[0076] The preparation method comprises the following steps:

[0077] Graphite, SBR, CB, CMC and N-methylpyrrolidone (NMP) were mixed to a solid content of 45% (by volume) and stirred to prepare a primer slurry. The primer slurry was then applied to both sides of a copper foil with a thickness of 8 μm in a magnetic field environment. The copper foil coated with the slurry was baked in an oven and then rolled and slit to obtain the negative electrode current collector.

[0078] Example 2-13

[0079] The negative electrode current collector provided is substantially the same as that in Example 1, with the only difference being that the parameters shown in Table 1 are changed.

[0080] Comparative Examples 1-5

[0081] The negative electrode current collector provided is substantially the same as that in Example 1, with the only difference being that the parameters shown in Table 1 are changed.

[0082] Application Example 1

[0083] 1) The negative electrode current collectors of the above embodiments and comparative examples were used to prepare negative electrode sheets. The negative electrode sheets included negative electrode current collectors and negative electrode active layers on both surfaces of the negative electrode current collectors. The thickness of the negative electrode active material layers was 120 μm. The surface density of the negative electrode sheet was 200 mg / cm 2 The negative electrode active material layer comprises, by mass, 95.7 parts of graphite, 0.96 parts of conductive carbon black, 1.91 parts of carboxymethyl cellulose and 0.96 parts of styrene-butadiene rubber; and the preparation method specifically comprises the following steps:

[0084] Graphite, conductive carbon black, styrene-butadiene rubber, and carboxymethyl cellulose were added to NMP to make the solid content of the slurry reach 45% (by volume), and stirred to prepare the negative electrode active layer slurry. Then, the bottom negative electrode active layer slurry was coated on both sides of the negative electrode current collector in a magnetic field environment with a thickness of 1000 nm. The negative electrode current collector coated with the slurry was baked in an oven, and then rolled and cut to obtain the negative electrode sheet. The negative electrode sheet was compacted to 1.60 g / cm 3 .

[0085] 2) A negative electrode sheet was prepared using a blank copper foil with a thickness of 8 μm. The preparation method was referred to the above operation 1). The prepared negative electrode sheet was recorded as blank.

[0086] Application Example 2

[0087] The negative electrode sheets of the above-mentioned application example 1 are respectively used to assemble batteries, which includes the following steps:

[0088] Preparation of positive electrode sheet: The positive electrode active material LiFePO4, polyvinylidene fluoride and acetylene black were mixed in a weight ratio of 95.7:0.96:1.91, and then N-methylpyrrolidone was added and stirred in a vacuum mixer until the mixture formed a positive electrode slurry with uniform fluidity (N-methylpyrrolidone accounted for 55% by volume); the positive electrode slurry was evenly coated on an aluminum foil with a thickness of 8μm; the coated aluminum foil was baked in an oven with different temperature gradients, and then dried in an oven at 120°C for 8 hours, and then rolled and slit to obtain the desired positive electrode sheet;

[0089] Preparation of electrolyte: Ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC) = 2:5:3 mass ratio after mixing, add 5% of the total mass of the electrolyte fluoroethylene carbonate (FEC) and 13% of the total mass of the electrolyte lithium hexafluorophosphate (LiPF6), mix and stir to obtain the electrolyte

[0090] Assembled batteries: Each battery consists of one electrode core, and each electrode core consists of 7 positive electrode sheets, 8 negative electrode sheets and 16 separators prepared as described above, wherein the excess ratio of the negative electrode is 15%.

[0091] Test Case

[0092] The peeling force and longitudinal resistivity of the negative electrode sheets of the above-mentioned embodiments and comparative examples were tested, and the results are recorded in Table 2.

[0093] The peeling force test method is as follows: the pressure-sensitive adhesive tape is bonded to a stainless steel plate, and then a fixed area (40×100mm 2 ) is bonded to a pressure-sensitive tape on one side of the negative electrode active material layer of the negative electrode sheet. The tensile testing machine clamps the negative electrode sheet and peels it off at 180°. The force required to peel the negative electrode active material layer off the copper foil is the peeling force.

[0094] Longitudinal resistivity test method: Cut the negative electrode sheet into 4×10cm samples, place the samples in the resistivity test bench, set the test pressure to 25KPa, and hold the pressure for 20s. The test result is the longitudinal resistivity of the electrode sheet.

[0095] The 50% SOC DC internal resistance and gram capacity of the battery made with the corresponding negative electrode sheet were tested. The test results are shown in Table 2.

[0096] Among them, the 50% SOC DC internal resistance test method: at room temperature 25±5℃, the battery is discharged to 2.0V at a constant current of 1 / 3C, charged to 50% SOC at a constant current of 1 / 3C, and left for 30 minutes; discharged at a constant current of 1.5C for 30 seconds, and the 50% SOC DC internal resistance is detected.

[0097] Mixed material gram capacity test method: At room temperature 25±5℃, the battery is discharged at 1 / 3C constant current to 2.0V, and charged at 1 / 3C constant current and constant voltage to 3.8V, with a cut-off current of 0.05C, and cycled for 3 cycles; the discharge capacity in the third cycle is the battery capacity, and the mixed material gram capacity = battery capacity / positive electrode dressing amount.

[0098] Table 1:

[0099] SBR addition amount CB addition amount OI value Base coating thickness magnetic field <![CDATA[(g / 100g 石墨 )]]> <![CDATA[(g / 100g 石墨 )]]> μm Yes / No Example 1 1.5 2 3 15 have Example 2 2 2 3 15 have Example 3 1.2 2 3 15 have Example 4 1.8 2 3 15 have Example 5 1.5 3 3 15 have Example 6 1.5 0.5 3 15 have Example 7 1.5 1 3 15 have Example 8 1.5 2.5 3 15 have Example 9 1.5 2 3 25 have Example 10 1.5 2 3 5 have Example 11 1.5 2 3 26 have Example 12 1.5 2 3 10 have Example 13 1.5 2 3 20 have Comparative Example 1 2.5 2 3 15 have Comparative Example 2 1.5 3.5 3 15 have Comparative Example 3 0.8 2 3 15 have Comparative Example 4 1.5 0.3 3 15 have Comparative Example 5 1.5 2 10 15 none

[0100] Table 2:

[0101]

[0102]

[0103] It can be seen from Table 2 that, from the perspective of the electrode, compared with the comparative example, the electrode of the embodiment can have both higher electrode peeling force and lower resistivity; from the perspective of the battery, compared with the comparative example, the electrode of the embodiment is used to assemble the battery, which is beneficial to ensure that the first efficiency of the battery is not reduced, has a lower 50% SOC DC internal resistance and a higher mixed material gram capacity under the same conditions.

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode current collector, characterized in that The invention comprises a metal base layer and a base coating layer provided on at least one functional surface of the metal base layer; the base coating layer comprises an active material, a binder and a conductive agent; the active material comprises graphite; the binder content in the base coating layer is 1.2-2 g / 100 g 石墨 , the content of conductive agent is 0.5-3g / 100g 石墨 ; The OI value of the negative electrode current collector is not greater than 5.

2. The negative electrode current collector according to claim 1, characterized in that The thickness of the primer layer is L, and L satisfies: 5 μm≤L≤25 μm.

3. The negative electrode current collector according to claim 2, characterized in that 10μm≤L≤20μm.

4. The negative electrode current collector according to any one of claims 1 to 3, characterized in that: The content of the binder is 1.3-1.8g / 100g 石墨 ; And / or, the content of the conductive agent is 1-2.5g / 100g 石墨 .

5. The negative electrode current collector according to any one of claims 1 to 4, characterized in that: In the binder, the proportion of styrene-butadiene rubber is not less than 60 wt %, and in the conductive agent, the proportion of conductive carbon black is not less than 60 wt %.

6. A method for preparing a negative electrode current collector according to claims 1-5, characterized in that: The following steps are involved: The negative electrode current collector is obtained by coating a slurry containing an active material, a binder and a conductive agent on at least one functional surface of the metal bottom layer and performing a drying treatment in a magnetic field environment.

7. A negative electrode sheet, characterized in that: The negative electrode current collector comprises the negative electrode current collector according to any one of claims 1 to 6 and a negative electrode active layer arranged on the surface of at least one primer layer of the negative electrode current collector.

8. A battery, characterized in that: Including the negative electrode sheet according to claim 7.

9. A battery pack, characterized in that: A battery comprising the battery of claim 8.

10. An electrical device, characterized in that: Comprising the battery according to claim 8 or the battery pack according to claim 9.